2015
DOI: 10.1007/s11032-015-0360-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci associated with soybean resistance to common cutworm and soybean compensatory growth after defoliation using SNP marker-based genome-wide association analysis

Abstract: Resistance and tolerance are different plant defense mechanisms against herbivores. In this study, four compensatory growth (tolerance) indexes-the ratios of treatment to control for plant height (RPH), branching number of the stem (RBN), seed number per plant (RSN), and seed weight per plant (RSW)-and three resistance indexes-larval weight (LW), pupal weight (PW), and larva-consumed leaf weight (LCL)-were used to evaluate soybean (Glycine max (L.) Merr) defense against common cutworm (CCW; Spodoptera litura F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Few GWASs of soybean insects or other pests such as nematodes have been carried out, and these studies have generally found few SNPs associated with resistance (Wang et al, 2015; Vuong et al, 2015; Liu et al, 2016; Chang and Hartman 2017). Because of the number of significant SNPs found in this study for each biotype, there appears to be significant genetic variation associated with soybean aphid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Few GWASs of soybean insects or other pests such as nematodes have been carried out, and these studies have generally found few SNPs associated with resistance (Wang et al, 2015; Vuong et al, 2015; Liu et al, 2016; Chang and Hartman 2017). Because of the number of significant SNPs found in this study for each biotype, there appears to be significant genetic variation associated with soybean aphid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean resistance mapping using GWAS has been demonstrated on a variety of diseases (Wen et al, 2014 ; Vuong et al, 2015 ; Chang et al, 2016c ) and the resistance mechanisms have been detailed for many important soybean diseases (Whitham et al, 2016 ). However, there are just a few GWAS focusing on soybean insect resistance like that of the common cutworm (CCW, Spodoptera litura Fabricius) (Wang et al, 2015 ; Liu et al, 2016 ). With the availability of GRIN phenotypic data and SoySNP50K genotypic data, the aim of our study was to integrate the information for discovering novel insect resistance sources in the USDA Soybean Germplasm Collection and highlight candidate resistance genes for each insect.…”
Section: Discussionmentioning
confidence: 99%
“…The power of GWAS has been well recognized in numerous studies, including those on soybean agronomic traits (Zhou et al, 2015 ) and on soybean disease resistance (Chang et al, 2016a , b , c ). There are fewer GWAS focusing on insect resistance in soybean (Wang et al, 2015 ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… Ghione et al (2021) found four markers associated with resistance genes against stink bugs using the association mapping strategy. To date, several insect-resistance QTLs, specific for leaf-chewing insects, have been identified in the soybean germplasm ( Rector et al, 2000 ; Zhu et al, 2008 ; Wang et al, 2015 ; Ortega et al, 2016 ; Sabljic et al, 2020 ; Ghione et al, 2021 ; Lucini et al, 2021 ). Interestingly, Ortega et al (2017) reported that the Glyma.07g110300 marker (encoding a UDP-glycosyltransferase) in QTL-M was a functional single-nucleotide polymorphism (SNP) that could be used for the marker-assisted selection of insect-resistance QTLs and Glyma.07g110300 exhibits a loss of function in insect-resistant soybean germplasms.…”
Section: Introductionmentioning
confidence: 99%